104: Regional Adiposity Is Not Associated with Vitamin D Status in Overweight and Obese School-Aged Children. Issue 6 (1st June 2014) - Kasvis, P; Cohen, TR; Loiselle, S; Kim, N; Hazell, TJ; Vanstone, CA; Agellon, S; Rodd, C; Plourde, H; Weiler, HA
Abstract: BACKGROUND: Vitamin D status is lower in Canadian children who are overweight or obese than in healthy weight children. OBJECTIVES: This study explored the association between regional adiposity and vitamin D status in overweight and obese children. DESIGN/METHODS: Baseline data was collected from participants enrolled in the McGill Youth and Lifestyle Intervention with Food and Exercise (MYLIFE) study; healthy children six to 12 years of age with BMI-for-age >85th percentile were included. Vitamin D status was assessed using plasma 25-hydroxyvitamin D (25(OH)D) concentration (chemiluminescence immunoassay). Standard measurements of weight, height and waist circumference (WC) were taken; BMI and BMI-z scores were calculated. Body composition was measured using dual-energy X-ray absorptiometry. Constitutive and facultative skin pigmentation was measured using a hand-held spectrophotometer in order to determine Fitzpatrick skin types. Children were categorized according to cutaneous UVB synthesis period. Ethnicity was self-disclosed and pubertal status was reported and categorized according to Tanner stages. Differences among categories were tested using a mixed model ANOVA. RESULTS: One hundred and twelve children (50 boys and 62 girls) took part in this study. The mean 25(OH)D concentration was 65.2±20.9 nmol/L, with no significant difference between sexes (P=0.723). Boys had lower percent body fat (%BF) (boys, 36.4±5.0%; girls, 38.4±4.8%; P=0.022) and greater BMI z-scores (boys, 3.4±1.1; girls, 2.8±0.7; P=0.004) than girls; no other differences were found between sexes for body composition. Plasma 25(OH)D concentrations were lower in fair-skinned compared to olive-skinned children (50.2±1.1 nmol/L vs. 67.5±1.1 nmol/L; P=0.025). Children of Caucasian mothers had greater 25(OH)D concentrations than those of African American mothers (74.0±1.1 nmol/L vs. 41.2±0.2 nmol/L, P=0.040); plasma 25(OH)D was not different according to paternal ethnicity nor child's sex, UVB period, age or pubertal status. There were no correlations between adiposity indicators (weight, fat mass (FM), %BF, android or gynoid FM, trunkal or appendicular FM, WC, BMI or BMI z-score) and 25(OH)D concentration, while accounting for sex, age, puberty, UVB period and skin colour. CONCLUSIONS: The vitamin D status of the children in this study was similar to that of national surveillance studies, although many fair-skinned children had low status (<50 nmol/L). Future longitudinal research is required to examine if a reduction in fat mass would lead to a concomitant increase in vitamin D status.